In-line monitoring of carbon nanoparticle epoxy dispersion processes: Insights into the process via next generation three roll mills and impedance spectroscopy - Meeuw, H.; Wisniewski, V. K.; Koepke, U.; Nia, A. S.; Vazquez, A. R.; Lohe, M. R.; Feng, X.; Fiedler, Bodo (Production Engineering, 2019)
The new generation of three roll mills is able to monitor occurring process loads while dispersion. This paper focuses on the interpretation of the gathered data to find criteria quantifying the dispersion state online. The aim is process time reduction. We used impedance spectroscopy to identify the dispersion state and correlated it with the occurring process loads. The dispersion process of a wide spectrum of carbon based nano particles, namely carbon black, single walled carbon nanotubes, multi walled carbon nanotubes, a few-layer graphene powder, electrochemically exfoliated graphite and a functionalized electrochemically exfoliated graphite was investigated. The filler content was varied along the material’s electrical percolation threshold. The criteria found led to a reduction of processing time and revealed the prevalent mechanisms during dispersion.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nano particle; Dispersion; Three roll mill